Clinical Radiology of Head and Neck Tumors - Nayak, Umanath (Springer Singapore, 2018)
This book is a quick reference guide to the radiology of head & neck tumors for busy clinicians. With the wide range of imaging modalities currently available and frequent upgrades in technology and image resolution, selecting the best modality for individual cases is not always easy. Balancing benefits of the investigation ordered with the costs incurred and inconvenience/risks as well as the clinician's familiarity with that particular imaging modality can be a daunting task. To aid in these decisions, this clearly written book includes case studies and focuses on the two most frequently used imaging modalities for head & neck tumors - CT and MR, presenting illustrations of clinical conditions, and where possible showing CT and MR images side-by-side for comparison.